Ki Hadjar Dewantara Educational Philosophy of Ngandel, Bandel, Kendel, and Kandel Portrayed on Mulan - Victa Sari Dwi Kurniati; Adhi Kusuma; Ima Widyastuti; Muhammad Amin Nadim; Riana Agustina (Universitas Sarjanawiyata Tamansiswa, 2023)
This study focuses on an analysis of Ki Hadjar Dewantara's Philosophy of Kandel, Bandel, Kendel, and Kandel as it relates to the main character in the Mulan (2020) Movie. The research examines the dialogue and scenes depicted in the film, followed by a thorough analysis of the characters using Ki Hadjar Dewantara's principles. According to the research, the film portrays Mulan as a character who possesses traits such as resilience, self-assurance, and bravery, which is evident in various scenes throughout the movie. Thus, the character of Hua Mulan is closely connected to the Ki Hadjar Dewantara principles of Ngandel, Bandel, Kendel, and Kandel.